OMERACT Definitions for Ultrasonographic Pathologies and Elementary Lesions of Rheumatic Disorders 15 Years On - Bruyn, George A; Iagnocco, Annamaria; Naredo, Esperanza; Balint, Peter V; Gutierrez, Marwin; Hammer, Hilde B; Collado, Paz; Filippou, Georgios; Schmidt, Wolfgang A; Jousse-Joulin, Sandrine; Mandl, Peter; Conaghan, Philip G; et al. (Journal of rheumatology, 2019)
The Outcome Measures in Rheumatology (OMERACT) Ultrasound (US) Working Group (WG) operates research activities for the validation of US as an outcome measurement instrument according to the Filter 2.0 framework. Original publications on definitions and scoring systems for pathophysiological manifestations and elementary lesions of various rheumatic disorders were reviewed from the onset of the WG research in 2005. Definitions and scoring systems according to new terminology are provided. We have redefined OMERACT US pathology and elementary lesions as well as scoring systems, which are now proposed for OMERACT approval for application in clinical trials.